Agile auditing at DBS: Embracing the future - FOO, See Liang (Institutional Knowledge at Singapore Management University, 2017)
The case describes the continuous efforts of Group Audit at DBS bank Singapore, to enhance the value of Internal Audit (IA) to the organisation as a function by adopting various methodologies to make IA more effective in providing added assurance to the bank on the adequacy of their internal controls. The case specifically focuses on Agile Auditing practices that DBS Group Audit implemented on a pilot basis in 2016 as a part of their Future of Auditing initiative, which was an approach aimed at making IA productive, proactive, predictive and preventive. It delves into the limitations of an audit approach and how introducing agile practices to IA can help overcome those limitations. It also tries to assess the additional benefits that an agile audit can bring to the table. The case attempts to analyse why and how agile auditing can make audit cycles more efficient and effective. An important aspect of IA is scope, and the case explores how agile auditing allows IA to move away from being scope bound, thus introducing flexibility in audit while still maintaining audit independence and quality. The case also delves into the decision making process that led to the adoption of the agile auditing methodology by the DBS Group Audit. It also discusses the strategy used by the Internal Audit team to gain stakeholder engagement and support to implement agile auditing within the organisation and examines the tools used by the team to assist in executing agile auditing. It elaborates on the SCRUM framework adopted by the team and the technology enablers that enabled the DBS internal audit team to execute their pilot Internal Audit projects successfully. The case also highlights the advantages that agile auditing brought to the table for DBS Group audit, and the uniqueness of it being one of the first departments within the organisation to adopt agile practices. The case also provides insight into how an agile approach to auditing can be successfully adopted in an organisation with minimal disruption within the existing team setup as opposed to a disruptive full scale agile adoption. This case study would enable students to understand the benefits that agile practices can bring to internal auditing. It will also help students understand some of the common problems faced in implementing agile practices.